2018
DOI: 10.1039/c8ta02237b
|View full text |Cite
|
Sign up to set email alerts
|

High oxide-ion conductivity in Si-deficient La9.565(Si5.8260.174)O26apatite without interstitial oxygens due to the overbonded channel oxygens

Abstract: Overbonding of the channel oxygens in the apatite-type lanthanum silicates was found to be a key for the high oxide-ion conductivities by the present single-crystal neutron and X-ray diffraction studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…The fluoride ions located around the center of the Pb 6 octahedron electrostatically attract Pb 2+ ions along the c axis. This attractive force acts to compress the unit cell, leading to shrinkage of the c axis and elongation of the a axis for Pb 5 (VO 4 ) 3 F. According to a previous study by Fujii et al, 17) the overbonding state of the X anion at the center of the triangular site (z = 0.25) in an apatite-type structure strongly correlates with high ionic conductivity. This instability leads to the diffusion of the anion along the c axis, resulting in high ionic conductivity.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The fluoride ions located around the center of the Pb 6 octahedron electrostatically attract Pb 2+ ions along the c axis. This attractive force acts to compress the unit cell, leading to shrinkage of the c axis and elongation of the a axis for Pb 5 (VO 4 ) 3 F. According to a previous study by Fujii et al, 17) the overbonding state of the X anion at the center of the triangular site (z = 0.25) in an apatite-type structure strongly correlates with high ionic conductivity. This instability leads to the diffusion of the anion along the c axis, resulting in high ionic conductivity.…”
Section: Resultsmentioning
confidence: 88%
“…18) 20) The fluoride ions located at the 4e site have the potential to exhibit fluoride ion conduction, as seen in La 3+ 9.333+x (Si 4+ O 4 ) 6 O 2+3/2x . As proposed by Fujii et al, 17) the interaction between A cations and fluoride anions is crucial for ion conductivity; thus, comparison between the fine structures of these apatites is essential for the estimation of their physical properties. In this study, we demonstrate that Pb 5 (VO 4 ) 3 F exhibits significantly different site selectivity of fluoride anions than Sr 5 (VO 4 ) 3 F and Ba 5 (VO 4 ) 3 F, suggesting its potential as a fluoride ion conductor.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…26 An apatite-type lanthanum silicate (LSO) with a structure of the P63/m space group, 27 which has a high σo, was used as a solid electrolyte to obtain a higher oxygen permeation flux than that of the YSZ or bismuthoxide-based solid electrolyte. LSO can be a promising solid electrolyte in the oxygen separation system because it not only has a high σo (0.01 S cm −1 at 400 °C) along the caxis 28 , but also a high oxide-ion transference number. 29 We synthesized a La9.66Si5.3B0.7O26.14 (c-LSBO) solid electrolyte with crystal orientation along the c-axis and reported a high σo (0.016 S cm −1 at 400 °C).…”
Section: Introductionmentioning
confidence: 99%
“…14) Fujii et al reported that La 9.33 Si 5.826 O 26 single crystal displays remarkably high oxide ionic conductivity of 1.04 © 10 ¹2 S cm ¹1 at 400°C. 15) In addition, the fabrication process for c-axis-oriented LSO ceramics with high ionic conductivity has been developed. 14),16), 17) Therefore, c-axis-oriented LSO seems to be a promising candidate for the solid electrolyte of oxygen separation systems operating at 400°C.…”
mentioning
confidence: 99%